A quarter-life crisis in early adulthood in Indonesia during the Covid-19 pandemic - Putri, Adita Lintang Kharisma; Lestari, Sri; Khisbiyah, Yayah (Indigenous, 2022)
Abstract. Quarter-life crisis in youngsters in their 20s triggered by concerns over uncertainties of future life, notably regarding job prospects, romantic relationships linked with marriage plan, and social life. The purpose of this study is to understand the psychosocial dynamics of the quarter-life crisis and to comprehend the impact of the Covid-19 pandemic on the quarter-life crisis among early adults in various regions in Indonesia. The research uses a phenomenological method of qualitative approach. Research participants were selected using the purposive sampling technique, composed of 6 people who experienced a quarter-life crisis. The age range of the participants was 20 to 29 years. Semi-structured interviews through Whatsapp media were used to collect the data. The data were analyzed with Interpretative Phenomenological Analysis (IPA). The results showed that work-related demands, marriage plans, and family-related issues are the root causes of quarter-life crises marked by disturbing negative thoughts and feelings. Pandemic Covid-19 has also intensified the anxieties felt by some participants as the economic situation and job prospects got even bleaker. This study implies that to prevent a quarter-life crisis among youth, families are expected to be more supportive by providing support and trust for young adults to make decisions and be responsible for their choices for the future.Keywords: content validity; confirmatory factor analysis; interreligious harmony.